2009
DOI: 10.1109/tasc.2009.2019142
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Characteristics in RF Magnetic Shielding Effects of BPSCCO Plates

Abstract: As one of the basic areas of research for improvement of the electromagnetic environment by use of a bulk high-critical temperature superconductor, the present paper has examined a Bi-Pb-Sr-Ca-Cu-O (BPSCCO) plate with a slit, which displays orientation characteristics in the RF magnetic shielding. According to the results, the value of the RF magnetic shielding degree HP , when orienting the slit of the BPSCCO plate perpendicular to the ground, increased in the frequency region of 1 MHz (20 dB) to 30 MHz (40 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…In Table 1, the length L, width w, and slit number N are listed for the optimum size of the slit plates for displaying the maximum orientation characteristics in RF magnetic shielding effects, as reported in Refs. [3,4]. It has been reported that the orientation characteristics for the slit ferrite plate are opposite to those for the slit carbon plate, in association with the value of characteristic impedance Z S (>Z 0 (=120π Ω), characteristic impedance of free space) for ferrite [3,4].…”
Section: Experimental Procedures 21 Fabrication Of the Slit Platesmentioning
confidence: 98%
See 4 more Smart Citations
“…In Table 1, the length L, width w, and slit number N are listed for the optimum size of the slit plates for displaying the maximum orientation characteristics in RF magnetic shielding effects, as reported in Refs. [3,4]. It has been reported that the orientation characteristics for the slit ferrite plate are opposite to those for the slit carbon plate, in association with the value of characteristic impedance Z S (>Z 0 (=120π Ω), characteristic impedance of free space) for ferrite [3,4].…”
Section: Experimental Procedures 21 Fabrication Of the Slit Platesmentioning
confidence: 98%
“…In the present research, use was made of commercial carbon (Toyo-Tanso, IG-110, 50 mm square, thickness of 1 mm) and ferrite (TDK, IB-015, 50 mm square, thickness of 2 mm) plates. Slits were cut in the surface of the carbon and ferrite plates by the use of a diamond saw, operated at a low cutting rate to prevent any influence of heat and cracking [4]. All slits were made through the entire thickness of the plates.…”
Section: Experimental Procedures 21 Fabrication Of the Slit Platesmentioning
confidence: 99%
See 3 more Smart Citations